2014
DOI: 10.1128/jvi.00268-14
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Association with Host and Viral Chromatin by Kaposi's Sarcoma-Associated Herpesvirus LANA and Its Reversal during Lytic Reactivation

Abstract: Latency-associated nuclear antigen (LANA), a multifunctional protein expressed by the Kaposi sarcoma-associated herpesvirus (KSHV) in latently infected cells, is required for stable maintenance of the viral episome. This is mediated by two interactions: LANA binds to specific sequences (LBS1 and LBS2) on viral DNA and also engages host histones, tethering the viral genome to host chromosomes in mitosis. LANA has also been suggested to affect host gene expression, but both the mechanism(s) and role of this dysr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 97 publications
11
53
0
Order By: Relevance
“…Although these studies have already depicted the genome-wide map of LANA-binding sites, it remains unclear whether LANA can modulate gene expression by directly binding to cellular chromosome DNA. The ChIP-seq results in BC-3 cells were highly consistent with those of previous studies, including the LANA-binding sequence and the enrichment of LANA at cellular TSSs (43)(44)(45). However, the different methods of analysis of the LANA ChIP-seq data demonstrated that LANA is enriched in the macromolecule catabolic process, which was overlooked in the previous studies that did not distinguish between direct LANA binding and indirect LANA binding.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although these studies have already depicted the genome-wide map of LANA-binding sites, it remains unclear whether LANA can modulate gene expression by directly binding to cellular chromosome DNA. The ChIP-seq results in BC-3 cells were highly consistent with those of previous studies, including the LANA-binding sequence and the enrichment of LANA at cellular TSSs (43)(44)(45). However, the different methods of analysis of the LANA ChIP-seq data demonstrated that LANA is enriched in the macromolecule catabolic process, which was overlooked in the previous studies that did not distinguish between direct LANA binding and indirect LANA binding.…”
Section: Discussionsupporting
confidence: 86%
“…We also found that SENP6 interacted with LANA and reduced the formation of sumoylated LANA, which relies on the desumoylation ability of SENP6. During de novo infection, SENP6 overexpression decreased the (E) Venn diagram of promoters directly bound by LANA in the present study and previously published data (43)(44)(45). (F) The overlapping genes identified in the present study and previously published data (43)(44)(45).…”
supporting
confidence: 81%
“…KSHV establishes a latent infection in most infected cells, whereas a small proportion of cells develop lytic infection. The genetic profiles of KSHV-infected populations differ from those of uninfected populations, with host cell transcriptional remodeling observed in latently KSHV-infected cells (4) and global mRNA shutoff noted during lytic replication (5,6).…”
mentioning
confidence: 99%
“…LANA mediates transcriptional upregulation and downregulation (32). Chromatin immunoprecipitation (ChIP) analyses have found LANA associated with the same sequences in the host genome as were characterized in the viral terminal repeats, in association with a separate characterized binding motif and binding indirectly through protein-protein interactions (33)(34)(35). LANA participates in epigenetic silencing (36)(37)(38)(39), increased transcription factor activity (40)(41)(42)(43)(44)(45)(46), and modulation of interferon signaling (33,47), the cell cycle (42,48,49) and kinase activity (50)(51)(52)(53)(54).…”
mentioning
confidence: 99%